My x, y, z Book - Moncure, Jane Belk.; Hohag, Linda; Moncure, Jane Belk. (Elgin, Ill., 1984)
Little x, Little y, and Little z fill their boxes with things that begin with the letters x, y, and z.
Rev. ed. of: My x, y, z sound box. c1979.
Keywords: Children's stories, American